A Review Study on the Strategic Importance of Human Capital Through Education in Driving Socio-Economic Development - Khan, Farah; Fauzee, Mohd Sofian Omar (Innovare Journal of Education, 2025)
Human capital through education is the most important key factor in production/output (national income) and, therefore, in the socio-economic development of any country. Education fosters workers’ creativity and productivity, promotes entrepreneurship, and contributes to socio-economic development. The main aim of the present study is to increase understanding of the indispensable role played by education in promoting social welfare. After reviewing prior theoretical and empirical studies, the results indicate that education is the most significant factor in the process of socio-economic development and, thereby, sustainable development goals of the United Nations. The results of the present study recommend that policymakers focus on promoting the education sector. Consequently, this will further enhance the social welfare of the people.